Morphological remarks in the ghost shrimp callichirus seilacheri (Bott, 1955) (decapoda, callianassidae) - Hernáez, Patricio [UNESP]; Granda-Rodríguez, Hernán; Rio, Juliana Priscila Piva [UNESP]; Pinheiro, Marcelo Antonio Amaro [UNESP] (Boletim do Instituto de Pesca, 2018)
Callichirus seilacheri (Bott, 1955) is considered one of the most common ghost shrimps in the intertidal zone of sandy beaches along the eastern tropical Pacific. The present study provides new observations on the morphology of C. seilacheri, based on the revision of abundant material collected along the Pacific coast of Central America, including specimens from the type locality (Playa Los Blancos, El Salvador) of this species. The new features of C. seilacheri include: carapace with low triangular rostrum, without setae on tip; pereiopod 1 highly dissimilar in adult males, but not in females and juveniles of both sexes; first pleopod sexually dimorphic; females with oval gonopores, each one of them on the ventral coxal segment of the third pereiopod, and extra genital pores on the ventral coxal segment of the fifth pereiopod, these latter non-functional (non connected with the ovaries). Apparently, the presence of extra gonopores in females of C. seilacheri is a vestigial character shared with other representatives of the same genus.
Observações morfológicas no camarão-fantasma callichirus seilacheri (Bott, 1955) (decapoda, callianassidae)
Keywords: Axiidea; Diagnosis; Eastern Pacific; Gonopores; Intertidal macroinvertebrates